Awareness and Practices of Food Hygiene Regulation among Food Vendors in Negeri Sembilan - Pakir Mohamed, Mohamed Ismail; Fatin Natazlyana Nor Azizi, (Research in Management of Technology and Business, 2021)
A previous study reported that Negeri Sembilan, one of the states in Malaysia, has shown an increasing trend in implementing food hygiene practices among food industry stakeholders. However, even though there is an increasing trend in implementing food hygiene practices, foodborne illness and food poisoning cases still occur in Negeri Sembilan. Therefore there is a need to evaluate FHR awareness and practice among the local food vendors in Negeri Sembilan. A quantitative approach using survey methods via face-to-face interview method and an online platform (Google Form) was conducted which involved a total of 205 respondents Personal hygiene, Equipment hygiene, and Premise hygiene was used to measure the food hygiene practices and the relationship with the level of awareness on Food Hygiene Regulation among respondents. Correlation and descriptive data analysis using Statistical Package for Social Science (SPSS) revealed that the level of awareness on Food Hygiene Regulation among the respondents is high. It is also discovered that there is a significant relationship between food hygiene practices and the level of awareness on Food Hygiene Regulation of the respondents. So it can be concluded that the level of awareness on food hygiene practices such as  Personal hygiene, Equipment hygiene, and Premise hygiene is important to achieve food safety and the fulfillment of FHR in Negeri Sembilan. Therefore to increase food safety standards. more work needs to be done to increase the level of awareness among food vendors in Negeri Sembilan.